(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present study is for examining the problems of rural entrepreneurs in Tirunelveli. The results of the study setup that ’shortage of finance’, shortage in marketing’, ’defined mobility’, ’inadequate of managerial skills’, ’technical experience’, inadequate of modernization’, ’work life imbalance, ’lack of awareness’, ’lack of skilled manpower’, ’inadequate supply of power’, ’insufficient supply of inputs’, ’cut throat competition’, ’inflation’ and ’reducing subsidies’ are the fourteen problems that have an opposite impact over the growth of rural entrepreneurship in Tirunelveli. The significant value of Kendall Coefficient of Concordance signifies that there is a close concordance among the perceptions of respondents pertaining to the statements designed for the study. The findings of the present study will be very useful for the various stakeholders’ viz., centre and state governments especially dealing with the micro and small scale industry, non-governmental organizations etc. to formulate the effective policy for the promotion of rural entrepreneurship in our economy.